Effects of FeCrC and FeSiCrC particles on wear behaviour of aluminium metal matrix composite - Buytoz, S (Maney Publishing, 2006)
The tribological behaviour of Al-FeCrC(p) and Al-FeSiCrC(p) composites produced by the stir cast method was studied under dry sliding conditions against AISI 4340 steel, using a pin on ring aparatus. The effect of the composites on the wear behaviour of primary M7C3 carbides and secondary Al3Fe and alpha-AlFeSi phases in all composites was investigated. The hardness values were changed between 68 and 120 HB for composite materials. The peak hardness was measured to be 120 HB for Al-15FeSiCrC((p)) ( vol.-%) composite. The hardness values of other composites were also increased when the particle content was increased. Worn test specimens were examined by scanning electron microscopy, and wear mechanisms were determined. The particulates are distributed uniformly within the aluminium alloy matrix as well as the improved wear characteristics when compared with the base alloy. Increasing applied load increased the wear rate. However, the wear rate was decreased as a function of the sliding distance.
Keywords: metal matrix composite; M7C3 carbide; wear; particle reinforcement